FAKTOR-FAKTOR YANG MEMPENGARUHI EARNINGS QUALITY PADA PERUSAHAAN CONSUMER GOODS DI INDONESIA - Auria, Irda; Bangun, Nurainun (Fakultas Ekonomi, Universitas Tarumanagara, 2023)
The purpose of this study was to determine the effect of the investment opportunity set, free cash flow, and leverage on earnings quality. The population in this study are consumer goods sector companies listed on the Indonesia Stock Exchange in 2018-2020. The sampling method used was purposive sampling with predetermined criteria. Earnings quality is determined by discretionary accruals. The results of this study stated that the investment opportunity set and free cash flow did not have a significant effect on earnings quality. While leverage had a significant effect on earnings quality.